A system for online compression of high-speed network measurements. (29th September 2008) - Kyriakopoulos, Konstantinos G.; Parish, David J.
Measuring metrics of high-speed networks produces large amounts of information over long periods of time, making the conventional storage of the data practically inefficient. Such metrics are derived from packet information and can be represented as time series signals. This paper looks at the Wavelet transform as a method of analysing and compressing measurement signals. A live system calculates these measurements and performs wavelet techniques to preserve the significant information and discard the small variations. An investigation of an appropriate wavelet is presented along with results from off-line and on-line experiments. Finally, a comparison of compression performance is presented against bzip2.